(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
This article presents a comprehensive linguistic analysis of intonation with a systematic identification of the most important functions and features of the phonetic design of this phenomenon based on the American film "Clueless". Due to the fact that the action of the film takes place at school and touches upon the problem of social groups among young people, the characters’ speech is filled with jargon and speech phenomena accompanying intonation (in particular, Vocal Fry, a discursive marker like), and demonstrates the use of this intonation. It is important to note that the index, or personal-social function of intonation is of the greatest value in this study, i.e. “The ability of intonation to identify the speaker’s personality”.